¬Antidiabetic Activity of Ethanol Extract of Tetracera scandens (L.) Merr. Stems - Fauziah, Fitra; Kardela, Widya; Tinsia, Dwi Julda (Asian Journal of Pharmaceutical Research and Development, 2022)
Diabetes mellitus is a metabolic disorder which had a high prevalence in Indonesia. Traditional medicinal plants have been developed to treat diabetes mellitus. One of them is Tetracera scandens (L.) Merr.This study aimed to determine the antidiabetic activity of the ethanol extract of T.scandens stems on blood glucose levels, insulin levels, and homeostatic model assessment for insulin resistance (HOMA-IR) in mice induced by alloxan. Animals were grouped into five groups: normal group, negative control, and extract doses of 175, 350, and 700 mg/kg BW. Animals were induced with an alloxandose of 175 mg/kg BW. The extract was given orally for 21 days.The results showed that the administration of ethanol extract ofT.scandens stemscould significantly reduce blood glucose levels, increase insulin levels and reduce insulin resistance (p<0.05).It can be concluded that the ethanol extract of T.scandens potential to develop as herbal medicine in diabetes mellitus therapy. Further study is needed toconfirmthe antidiabetic activity of T.scandens.